Emission of selected halocarbons by seaweeds inhabiting a coral reef / Fiona Keng Seh Lin - Keng, Fiona Seh Lin (2013)
Since the discovery of the Antarctic stratospheric ozone hole in 1985 there has been increasing scientific interest in the halocarbon species that can cause ozone destruction. Although an important region for halocarbons in terms of atmospheric circulation, the tropics are underrepresented in terms of halocarbon measurements, especially those biogenic short-lived halocarbon compounds. A fringing coral reef flat at Cape Rachado, west coast Peninsular Malaysia was selected for a study on the emissions of halocarbons by seaweeds. A portable, automated gas chromatograph with electron capture detector was used to measure a suite of halocarbon species trimonthly over a 15-month period at the study site. The measurements of the halocarbon atmospheric mixing ratios were then correlated to the seaweed standing biomass to investigate its influence on the halocarbon mixing ratios at the survey site. Although it was found that the atmospheric mixing ratio for the biogenic halocarbon compounds were poorly correlated (ρ < 0.5) to some of the important seaweed species at the sampling site, there was no significant correlation between the total seaweed standing biomass with the atmospheric concentration of biogenic halocarbon compounds. This may be due to many contributing factors such as localized emissions, wind direction and speed that might influence the halocarbon contents in the atmosphere. To better understand the halocarbon emissions by the seaweeds, a laboratory-based incubation study was conducted to observe if the halocarbon emissions by the seaweeds varied with irradiance. Three selected seaweed species, Sargassum binderi Sonder ex J. P a g e | i v Agardh, Padina australis Hauck, and Turbinaria conoides (J. Agardh) Kützing were collected from the sampling site and exposed to a range of irradiance in the laboratory. The halocarbon contents in the seawater were then analyzed using a purge-and-trap system attached to a gas chromatograph with mass selective detector. Release of halocarbons especially dibromochloromethane, CHBr2Cl (r= 0.79; p< 0.01) was found to be influenced by irradiance. Correlations were also observed between emission of certain halocarbons with photosynthetic activity, especially bromoiodomethane, CH2BrI (r = 0.85; p< 0.01) and bromoform, CHBr3 (r = 0.79; p< 0.01) suggesting that environmental factors such as light can affect the release of these volatile halogenated compounds by the seaweeds into the atmosphere. From this study, it was also found that upon comparison with temperate and polar brown seaweeds, tropical species, such as Turbinaria conoides, may emit higher levels of bromoform, CHBr3 and other halocarbons. It is therefore important to investigate the contribution of tropical seaweeds towards the local atmospheric composition of halocarbons.